Theoretical Calculations of Thermodynamic Properties of Small Halogen-Containing Molecules: Assessment of Reliability - Finch, Arthur; P.B. Sandall, John (Asian Journal of Chemistry, 2010)
With emphasis on enthalpies of formation, the reliability of recent all-valence-electron MNDO SCF-MO calculations with complete geometry optimisation have been assessed by comparison of computed and experimental values for selected halogen containing compounds.